1992
DOI: 10.1086/646512
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Central Venous Catheter Removal on the Recurrence of Catheter-Related Coagulase-Negative Stahylococcal Bacteremia

Abstract: Although patients with catheter-related coagulase-negative staphylococcal bacteremia could be treated successfully while the catheter remains in place with the majority remaining free of recurrence, catheter retention results in a significantly higher risk for the recurrence of the bacteremia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
2

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(31 citation statements)
references
References 31 publications
0
29
0
2
Order By: Relevance
“…39 Studies using 7 to 21 days of antibiotics infused through the infected line, primarily with BSIs caused by coagulase-negative staphylococci, have shown success rates of 60-91% without catheter removal, 39,47-49 although patient response varied significantly, depending on infecting microorganism; with coagulase-negative staphylococcal BSIs, the risk of recurrent bacteremia has been approximately 20%. 39,50,51 Several studies have reported successful treatment of IVD BSIs due to Candida spp. without device removal using prolonged courses of amphotericin B (AmB) administered through the catheter; 15,52,53 however, this is in contrast to the results of other prospective studies that have found an increased duration of candidemia and mortality in patients who retain their infected IVD.…”
Section: Diagnostic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Studies using 7 to 21 days of antibiotics infused through the infected line, primarily with BSIs caused by coagulase-negative staphylococci, have shown success rates of 60-91% without catheter removal, 39,47-49 although patient response varied significantly, depending on infecting microorganism; with coagulase-negative staphylococcal BSIs, the risk of recurrent bacteremia has been approximately 20%. 39,50,51 Several studies have reported successful treatment of IVD BSIs due to Candida spp. without device removal using prolonged courses of amphotericin B (AmB) administered through the catheter; 15,52,53 however, this is in contrast to the results of other prospective studies that have found an increased duration of candidemia and mortality in patients who retain their infected IVD.…”
Section: Diagnostic Studiesmentioning
confidence: 99%
“…37,38 Central venous thrombosis can now be diagnosed by venography, 37,38 ultrasonography, 75 MRI, 76 or CT. While there are no prospective data to guide the optimal duration of antimicrobial therapy for IVDR BSIs, most coagulase-negative staphylococcal infections can be cured with only 5 to 7 days of therapy, 1,28,50,78 whereas most infections caused by other microorganisms can be adequately treated with 10 to 14 days of antimicrobial therapy. 28,55,78,79 These recommendations hold only as long as there are no complications related to the infection-endocarditis, septic thrombophlebitis, septic thrombosis, or metastatic infection, such as osteomyelitis-and the BSI clears within 72 hours of initiating therapy.…”
Section: Anti-infective Therapymentioning
confidence: 99%
“…Infection is one of the most common causes of catheter failure, as well as the most difficult to manage [11], most often requiring catheter removal [12]. While a variety of microorganisms have been found to cause such infections, CNS, specifically S. epidermidis, represents the leading cause of both intra- [13] and extravascular [14] catheter-associated infections.…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, la probabilidad de éxito de esta terapia combinada dependerá de varios factores, como son el sitio de la infección (si existe tunelitis o infección del reservorio estaría indicada la retirada del catéter, dada la baja probabilidad de erradicación) o el germen implicado en la misma (es más probable que exista respuesta adecuada si la infección está causa por un S. coagulasa-negativo que por un S. aureus). La recurrencia de bacteriemia tras un ciclo de tratamiento antibiótico intravenoso es más probable cuando se deja el mismo catéter que cuando se retira (68). Este hecho refleja la incapacidad de la mayoría de los antibióticos para conseguir una concentración terapéutica necesaria para matar a los microorganismos que componen el biofilm (69,70).…”
Section: Sellado Como Tratamiento De Las Infecciones Relacionadas Conunclassified